Morphometric Analysis of Furcation Areas of Multirooted Teeth in a Tunisian Population - Rym Mabrouk; Chiraz Baccouche; Nadia Frih (Hindawi Limited, 2020)
Aims. The aim of the study was to evaluate the morphological characteristics of furcation of permanent molars in Tunisian population. Materials and Methods. One hundred and four extracted maxillary and mandibular permanent molars were included in this study; comprising 34 maxillary first molars, 18 maxillary second molars, 33 mandibular first molars, and 19 mandibular second molars. For each tooth, the vertical dimension of the root trunk, root length, and interradicular space width were assessed with a micrometer caliber. Different types of root trunk in maxillary and mandibular molars were also analyzed. Statistical analysis was performed using a t-test. Results. Root length decreased from the first to the second molars. This decrease seems to be pronounced at mandibular molars. The most observed root trunk type was type B, with a prevalence of 67.30% in maxillary molars and 51.92% in mandibular molars. The root trunk length increased from the first to the second molars in both maxillary and mandibular. The average width of the interradicular spaces varied on the same tooth and between the teeth. Conclusion. This study provides epidemiological data about molars root length, interradicular space, and root trunk vertical dimension in a Tunisian population that could help clinicians in periodontal and endodontic therapy.